2018
DOI: 10.1093/ecco-jcc/jjy163
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Colectomy and Colorectal Cancer After Appendectomy in Patients With Ulcerative Colitis: A Systematic Review and Meta-analysis

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…By altering metabolite levels and impairing host immune responses, persistent dysbiosis can promote the development of various diseases such as inflammatory bowel disease, celiac disease, cardiovascular disease, DM, rheumatoid arthritis, osteoarthritis, and even neurologic disorders via the brain-gut axis [20][21][22][23][24][25][26][27] . A significant association between appendectomy and these diseases has been observed in some large cohort studies [28][29][30][31][32][33][34] . www.nature.com/scientificreports/ Dysbiosis has also been linked to lung, breast, and GI cancers [5][6][7][8][12][13][14] .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…By altering metabolite levels and impairing host immune responses, persistent dysbiosis can promote the development of various diseases such as inflammatory bowel disease, celiac disease, cardiovascular disease, DM, rheumatoid arthritis, osteoarthritis, and even neurologic disorders via the brain-gut axis [20][21][22][23][24][25][26][27] . A significant association between appendectomy and these diseases has been observed in some large cohort studies [28][29][30][31][32][33][34] . www.nature.com/scientificreports/ Dysbiosis has also been linked to lung, breast, and GI cancers [5][6][7][8][12][13][14] .…”
Section: Discussionmentioning
confidence: 79%
“…Second, irritable bowel disease and pre-existing adenomas were not taken into account in the risk analysis. Considering the fact that irritable bowel disease might be suppressed by appendectomy and colonic adenomas are premalignant lesions, they are potential hidden confounding factors 28 , 29 . Third, the follow-up period in our study was shorter than the conventional follow-up period of 10 years, which is based on the time frame (7–10 years on average) of the adenoma to carcinoma transition 15 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It is concerning that some studies have suggested there may be an increased risk of high‐grade dysplasia and colorectal cancer in patients with ulcerative colitis who have undergone appendicectomy. However, a recent systematic review and meta‐analysis suggested that this may be due to colectomy being postponed owing to the positive effect of appendicectomy on disease activity. This highlights the need for close surveillance after appendicectomy, because ongoing (subclinical) inflammation increases the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results are not in agreement with previous studies. A meta‐analysis that investigated the colectomy rate in 10 studies, including 72 423 UC patients in total, did not find significant differences between patients with and without appendectomy (OR 1.25) [12]. These studies included colectomies indicated for active UC as well as colorectal neoplasia, and a shift was seen after appendectomy with fewer colectomies required for refractory colitis but more for colorectal neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, studies are emerging that demonstrate an increased colectomy rate, and remarkably an increased colorectal cancer (CRC) rate, after appendectomy in UC [10,11]. A recent systematic review and meta-analysis investigated these possible correlations in UC [12]. In this meta-analysis, the authors attempted to correct for possible confounding factors for developing CRC, including duration of UC disease, extent and severity of the disease, primary sclerosing cholangitis (PSC) and a family history for CRC [13].…”
Section: Introductionmentioning
confidence: 99%